Seven kings - Fultz, John R. (The books of the shaper ;, 2013)
In the jungles of Khyrei, an escaped slave seeks vengeance and finds the key to a savage revolution. In the drought-stricken Stormlands, the Twin Kings argue the destiny of their kingdom: one walks the path of knowledge, the other treads the road to war. Beyond the haunted mountains King Vireon confronts a plague of demons bent on destroying his family. With intrigue, sorcery, and war, Seven Kings continues the towering fantasy epic that began with Seven Princes.